(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2005)
Analysing the process of forming the Armenian ethnos and State system it is proved that the geological factors influence them, which cause the integrity and stability of the ethnos. We come to the conclusion that besides cosmic factors the active breakings of different order and their junctions, which are on the frontier belts of lithosphere plates also influence the forming of ethnogenesis zones and passionate atmosphere.